ZrOxNy decorative thin films prepared by the reactive gas pulsing process - Carvalho, P. (2009)
Zirconium oxynitride thin films were deposited by dc reactive magnetron sputtering. A zirconium metallic target was sputtered in an Ar + N2 + O2 atmosphere. Argon and nitrogen flow rates were maintained constant whereas oxygen was pulsed during the deposition, implementing the reactive gas pulsing process (RGPP). A constant pulsing period T = 3 s was used following an exponential periodic signal versus time. The introduction time of oxygen was systematically changed from 17% to 83% of the period. The RGPP allowed the synthesis of ZrOxNy films with tuneable metalloid concentrations adjusting the introduction time of the oxygen. Composition and structural variations associated with mechanical, optical and electrical properties exhibited a smooth transition, from metallic-like characteristics, typical of the fcc-ZrN phase, to semi-conducting behaviour corresponding to a mixture of orthorhombic-Zr3N4(O) and γ -Zr2ON2 crystalline phases.